PO.1.21 Attainment of EQ-5D-3L full health state after therapy is associated with decelerated organ damage accrual in systemic lupus erythematosus. (27th September 2022) - Lindblom, J; Zetterberg, S; Borg, A; Emamikia, S; Von Perner, G; Enman, Y; Heintz, E; Regardt, M; Grannas, D; Gomez, A; Parodis, I
Abstract : Purpose: Within the frame of a survey of the impact of patient-reported evaluation on long-term outcomes in systemic lupus erythematosus (SLE), we herein investigated whether attainment of self-reported full health state (FHS) following therapeutic intervention for active disease was associated with a lower probability to accrue organ damage. Methods: Data from the open-label (OL) extension periods of the BLISS-52 and BLISS-76 clinical trials of belimumab in SLE were used (N=973). FHS was defined as an experience of 'no problems' in all five dimensions of the EuroQol 5-Dimension health questionnaire three-level version (EQ-5D-3L). We also investigated potential associations between experience of 'no problems' in each one of the EQ-5D dimensions and organ damage accrual separately. Proportional hazards (Cox) regression analysis was employed for time-dependent associations between EQ-5D-3L responses at the OL baseline and the first documented increase in organ damage, as assessed using the Systemic Lupus International Collaborating Clinics (SLICC)/American College of Rheumatology (ACR) Damage Index (SDI). Results: FHS was associated with lower probability of and/or longer time to organ damage progression (adj. HR: 0.62; 95% CI: 0.38–0.99; P=0.047) after adjustment for potential confounders, as was experience of 'no problems' regarding mobility (adj. HR: 0.61; 95% CI: 0.43–0.87; P=0.006) and pain/discomfort (HR: 0.66; 95% CI: 0.44–1.00; P=0.049). No such association was seen in multivariable analyses for the other dimensions of EQ-5D; however, 'no problems' with regard to self-care showed a trend towards a statistically significant association with decelerated organ damage accrual (adj. HR: 0.65; 95% CI: 0.42–1.01; P=0.054). Conclusions: Experience of FHS and 'no problems' regarding mobility or pain/discomfort after therapeutic intervention for active SLE were associated with reduced subsequent risk of organ damage accrual, suggesting that optimisation of these health-related quality of life (HRQoL) aspects is a clinically relevant treatment target in patients with SLE.